YouTube’s Role in Nepal’s Media Landscape: Advancing Media Pluralism and Diversity - Acharya, Abinav (RR Interdisciplinary Journal, 2024)
This research explores the transformative role of YouTube in reshaping Nepal's media landscape, focusing on its implications for media pluralism and diversity. The primary purpose is to understand how YouTube, as a digital platform, influences traditional media structures, content diversity, and the broader socio-political discourse in Nepal. Employing a qualitative approach, the research integrates data analysis of findings collected from key stakeholders, including media professionals, content creators, and policy experts. Measuring variables include the diversity of content genres, the representation of marginalized voices, audience engagement metrics, and the impact of regulatory environment on content production and distribution. Findings suggest that YouTube has significantly democratized content creation, providing a platform for underrepresented groups and fostering a more pluralistic media environment. However, the research also identifies challenges, such as the prevalence of misinformation, regulatory ambiguities, and the economic sustainability of independent content creators. Recommendations include enhancing digital literacy programs, implementing clear regulatory frameworks to balance freedom of expression with accountability, and supporting sustainable business models for diverse media content. The study signifies the dual potential of YouTube to enrich media diversity while posing new challenges, highlighting the need to harness its benefits for Nepal's evolving media landscape.